Parental Relationship Status as a Moderator of the Associations Between Mothers’ and Fathers’ Conflict Behaviors and Early Child Behavior Problems - Lee, Shawna J. (Journal of interpersonal violence, 2022)
This study examines interparental conflict and associations with child behavior problems among a large, diverse sample of families with low income (N = 2,691) using path model analyses of mothers? and fathers? reports of constructive interparental conflict, destructive interparental conflict, and intimate partner violence (IPV) victimization at 15 months and child emotional insecurity and child behavior problems at 36 months. Multigroup models examined whether parental relationship status (i.e., married, cohabiting, and churning) moderated these associations. Fathers? perceptions of interparental conflict behaviors showed few direct associations with child outcomes, whereas mothers? perceptions of interparental conflict showed more robust associations with child outcomes. Specifically, mother-reported destructive conflict was associated with higher levels of child emotional insecurity and child behavior problems across parental relationship status subgroups. Mother-reported constructive conflict had a small negative association with child behavior problems in cohabiting families. Child emotional insecurity mediated the association of maternal destructive conflict on child behavior problems. Although churning families experienced higher levels of moderate and severe interparental conflict, associations linking destructive conflict to child behavior problems were consistent across parental relationship subgroups. There were few direct effects of father-reported constructive and destructive conflict on child well-being. However, the results supported the notion that fathers play an influential role in the family system via maternal reports of IPV victimization. Results of this study suggest that the mechanisms underlying emotional security theory, in which child emotional insecurity mediates the associations between maternal destructive conflict and child behavior problems, apply to a large and racially diverse sample of socioeconomically disadvantaged children.